Estimation of speciated and total mercury dry deposition at monitoring locations in eastern and central North America - L. Zhang; P. Blanchard; D. A. Gay; E. M. Prestbo; M. R. Risch; D. Johnson; J. Narayan; R. Zsolway; T. M. Holsen; E. K. Miller; M. S. Castro; J. A. Graydon; et al. (Atmospheric Chemistry and Physics, 2012)
Dry deposition of speciated mercury, i.e., gaseous oxidized mercury (GOM), particulate-bound mercury (PBM), and gaseous elemental mercury (GEM), was estimated for the year 2008–2009 at 19 monitoring locations in eastern and central North America. Dry deposition estimates were obtained by combining monitored two- to four-hourly speciated ambient concentrations with modeled hourly dry deposition velocities (Vd) calculated using forecasted meteorology. Annual dry deposition of GOM+PBM was estimated to be in the range of 0.4 to 8.1 μg m−2 at these locations with GOM deposition being mostly five to ten times higher than PBM deposition, due to their different modeled Vd values. Net annual GEM dry deposition was estimated to be in the range of 5 to 26 μg m−2 at 18 sites and 33 μg m−2 at one site. The estimated dry deposition agrees very well with limited surrogate-surface dry deposition measurements of GOM and PBM, and also agrees with litterfall mercury measurements conducted at multiple locations in eastern and central North America. This study suggests that GEM contributes much more than GOM+PBM to the total dry deposition at the majority of the sites considered here; the only exception is at locations close to significant point sources where GEM and GOM+PBM contribute equally to the total dry deposition. The relative magnitude of the speciated dry deposition and their good comparisons with litterfall deposition suggest that mercury in litterfall originates primarily from GEM, which is consistent with the limited number of previous field studies. The study also supports previous analyses suggesting that total dry deposition of mercury is equal to, if not more important than, wet deposition of mercury on a regional scale in eastern North America.